The State of Soils in the Semi-Desert Region of the Republic of Kalmykia - Altana Adyanova; Saglara Mandzhieva; Vishnu D. Rajput; Aleksey Buluktaev; Raisa Mukabenova; Nikita Dzimbeev; Vasiliy Sayanov; Aleksey Sherstnev; Anatolii Barahov (Journal of the Indian Society of Soil Science, 2023)
Global climate change, as a result of which further degradation of the Russian forest-steppe, steppe, and other arid zones is expected, which makes it necessary to pay special attention to the problems of the arid territories of Russia. The desertification of arid territories is largely connected with human activity. At the same time, the development of land degradation processes reached a critical level. The Republic of Kalmykia is the territory, which is suffered by long droughts, wind erosion, as well as inefficient use of water for irrigation, salinization of soil, overgrazing of livestock, unwarranted use of soil, and water-polluting chemicals. Desertification and land degradation in the Republic of Kalmykia have not only environmental but also negative socio-economic consequences. Thus, the purpose of this study is to identify changes in the chemical composition under the influence of anthropogenic load in the adjacent areas of Yashkul and Chernozemelsk districts of Republic of Kalmykia, Russia. Laboratory and analytical studies were performed using methods generally accepted in soil science (potentiometry, complexometry, analytical methods, and spectrophotometry). The content of organic carbon (OC) was estimated by sulfochromic oxidation, and the pH of the soil water suspension using a glass electrode in a 1:5 ratio. The chemical composition of soils was studied by X-ray fluorescence spectroscopy using a MAKS-GV spectroscan. In the process of research, the chemical composition of the soils of Kalmykia settlements was determined. It was revealed that the soils of the settlements of Yashkul and Chernozemelsk districts have the mean value of determining the content of organic matter in soil samples: 1.13% and 0.63% accordingly. In Yashkul district, the maximum values (1.89%) were recorded in the village of Ermeli, and the minimum values (0.31%) in the territory of the Chilgir village. In Chernozemelsk district, the maximum value (1.08%) was recorded in Adyk village in the school area, and the minimum value (0.10%) was recorded in Komsomolsky village. As per the content of humus in soils, it can be concluded that the soils are mostly low in humus. The pH of the soil solution is neutral or slightly alkaline in reaction, with signs of mineral salts in the soil.